A dental myth bites the dust: no observable relation between the incidence of dental abscess and the weather and lunar phase$dan ecological study - Ristow, Oliver; Koerdt, Steffen; Stelzner, Ruben; Stelzner, Matthias; Johannes, Christoph; Ristow, Melanie; Hohlweg-Majert, Bettina; Pautke, Christoph (BMC oral health, 2015)
Anecdotal reports assert a relationship between weather and lunar activity and the odontogenic abscess (OA) incidence, but this relationship has not been validated. Therefore, the present study investigated the relationship between oral pain caused by OA and a variety of meteorological parameters and cyclic lunar activity.
Gesehen am 25.06.2020